GEREJA SEBAGAI ORGANISASI NIRLABA: KETIKA NILAI-NILAI AKUNTANSI DAN LOYALITAS, MEMPENGARUHI INTENSI UMAT UNTUK BERDONASI - Panggabean, Jannes Samuel Elfronzo Abhimael; Panggabean, Marthin Elfritz (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
The recent revelation of corrupt behavior and fraud committed by certain church officials can undermine the trust of the congregation in the church’s financial management, ultimately reducing their intention to donate to the church. To address this issue, the church is urged to be transparent and accountable. This study aims to examine the influence of transparency, financial accountability, and the loyalty of the congregation to the church on their intention to donate. Data was obtained from 132 respondents across synods through a questionnaire. This study shows that transparency, financial accountability, and loyalty partially have a positive impact on the intention of the congregation to donate to the church. Through this research, the church is expected to provide optimal service to the congregation, including improving transparency and financial accountability, in order to maintain the loyalty of the congregation, which will ultimately increase their intention to donate to the church. Keywords: transparency; financial accountability; loyalty; congregation’s intention to donate; church. Terungkapnya perilaku koruptif dan kecurangan yang dilakukan oknum pengurus gereja beberapa waktu terakhir dapat menurunkan kepercayaan umat kepada pengelola keuangan gereja yang pada akhirnya dapat menurunkan intensi umat untuk berdonasi bagi gereja. Untuk mengatasi masalah tersebut, gereja didesak untuk transparan dan akuntabel. Penelitian ini bertujuan untuk menguji pengaruh transparansi, akuntabilitas keuangan, dan loyalitas umat kepada gereja terhadap intensi umat untuk berdonasi bagi gereja. Data diperoleh dari 132 responden lintas sinode melalui kuesioner. Penelitian ini menunjukkan bahwa transparansi, akuntabilitas keuangan, dan loyalitas berpengaruh positif terhadap intensi umat untuk berdonasi bagi gereja. Melalui penelitian ini, gereja diharapkan untuk memberikan pelayanan yang optimal kepada jemaat, termasuk meningkatkan transparansi dan akuntabilitas keuangan, agar loyalitas umat tetap terpelihara, yang pada akhirnya akan meningkatkan intensi umat untuk berdonasi bagi gereja. Kata kunci: transparansi; akuntabilitas keuangan; loyalitas; intensi umat untuk berdonasi; gereja.